'Should I get a PSA test?' – the question is not that simple. Issue 5 (September 2015) - Wibowo, Erik; Schellhammer, Paul F.; Montie, James E.; Lange, Paul H.; Goldenberg, S. Larry; Wassersug, Richard J.
<x xml:space="preserve">Abstract</x> PSA screening for prostate cancer is a controversial issue around the world. In this article the authors describe the situation in North America where screening is not being advised. They argue that patients should be tested and that men will adapt and learn to live with the results as active surveillance becomes more acceptable.